Congenital high airways obstruction syndrome – first and second trimester diagnosis. Issue 2 (May 2014) - Paoletti, Debra; Robertson, Meiri
Abstract: Congenital High Airways Obstruction Syndrome (CHAOS) is a rare condition associated with high fetal or neonatal mortality. Prenatal diagnosis in the second trimester is made by the typical ultrasound features of large echogenic lungs, a flattened or inverted diaphragm, and fetal ascites or hydrops. We present two cases diagnosed at our institution; one in the second trimester, and a first trimester diagnosis. To the best of our knowledge, first trimester diagnosis of CHAOS has not been previously reported.